The Notary's Liability Against the Cancellation of the Will by the Court which is detrimental to the Heirs - Isnanza Zulkarnaini; Liza Prihandhini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
A will is one method of inheritance. In the Civil Code Article 875, a will is a deed containing a statement by somebody about what he wants to occur after he dies and could be revoked. Giving will be given at a time when the giver will still be alive , but implementation will be done at the time the giver will die. The deed will be authentic . A Notary Public is an office general or office given public authority by the state to make deeds authentic . A Notary Public must make it good and true . If somebody feels harmed by the deed of a will made by a notary , then he could submit a lawsuit to the notary. A deed made by a notary could be null and void or revoked by a decision court if the material and formal requirements are not fulfilled . If revoked by a court decision, they lose their legal force, and if revoked by the parties involved, the deed becomes null and void. If you're a Notary Public, To make an error in making a deed so could bring penalty good in the form of penalty civil , sanctions administrative , sanction code ethics, even penalty criminal.